NUTRITIONAL IRON DEFICIENCY IN WOMEN OF CHILD BEARING AGE-WHAT TO DO? - Ansari, Tahir; Ali, Liaquat; Aziz, Tariq; Ara, Jamal; Liaquat, Nagina; Tahir, Humera (Journal of Ayub Medical College Abbottabad, 2009)
Background: Iron deficiency is the most common aetiology of anaemia worldwide and has several risk factors. Although iron deficiency anaemia (IDA) can occur at any age, women from reproductive age group are particularly vulnerable to develop IDA due to increased nutritional demand during pregnancy. Objective was to determine the frequency and nutritional risk factor of iron deficiency anaemia in women of child bearing age. This descriptive, cross sectional study was conducted from October 2005 to March 2006 at the Department of Medicine, Ward-5, and out-patients department of Jinnah Postgraduate Medical Centre, Karachi. Method: Two hundred non-pregnant females of child bearing age were included in the study; 100 with no previous pregnancy and remaining 100 with at least one prior history of pregnancy. All the relevant information, i.e., demographic and socioeconomic was collected through a questionnaire. Results: Two hundred patients with signs and symptoms of anaemia were recruited. Out of them 89 patients were found to be having iron deficiency anaemia in various age groups. Results also showed that dietary habit of patients was one of the causative factors leading to iron deficiency anaemia. Conclusion: To overcome iron deficiency anaemia a thorough and comprehensive strategy is required, i.e., educating the subjects to consume food rich in iron, community based program, monitoring severely anaemic cases and their treatment. Keywords: Nutrition, Iron deficiency anaemia, Child bearing age